PENGARUH PENGGUNAAN HANDPHONE TERHADAP HASIL BELAJAR SISWA DI KELAS IV SEKOLAH DASAR - Hutagaol, Robinson; Setiawati, Nanda Ayu; Silalahi, Taruli Marito; Br Saragih, Juli Siranihuta (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The purpose of this study was to analyze and determine how much influence the use of cellphones on student learning outcomes in grade IV SD Negeri 060833 Medan Petisah District. This research is a quantitative research which is included in the ex-post facto research. The population taken was the fourth grade students with a total of 22 students, of which 8 male students and 14 female students at SD Negeri 060833 Medan Petisah sub-district, with a total sample size of the total population. Data analysis used the One Kolmogrov-Smirnov data normality test and hypothesis testing with Simple Regression (Simple Regression). Based on the results of hypothesis testing using simple regression analysis, the effect of the use of mobile phones on student learning outcomes, the value of tcount = 2.701 ≥ (t table) = 2.079 with a significance of 0.491> 0.05, it can be concluded that there is an "Effect of Mobile Use on Student Learning Outcomes in SD Negeri 060833 Medan Petisah sub-district with a large contribution of 2.4%.